Ernst-Joachim Mestmäcker - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2008)
In the US, law and economics is so well established that many law schools have given up on a separate law and economics course. It seems obvious that economic theory matters for the interpretation and the evolution of the law. More recently, the empirical law movement has been gaining momentum which, in its majority, is an application of econometrics to legal issues. Compared to its American counterpart, German legal scholarship looks very different. Ernst-Joachim Mestmäcker has been one of the first German law professors to argue in economic terms, and he has always contrasted German with US law. Yet even this pioneer of a transnational perspective on German law cautions against the dangers of taking economics too seriously. He insists on the law being a tool for governing life, which excludes overly stringent methodology. In economic argument he misses freedom as a normative category that does not collapse with efficiency. He believes that evolutionary economics is much better suited to help the law than neoclassical models. And he is very critical of Richard Posner's work, which he dubs "A Legal Theory without Law".
Keywords: K00; K21; 330; law and economics; law and philosophy; Rechtsökonomik; Rechtsphilosophie; Wirtschaftswissenschaftler; Rechtswissenschaft; Deutschland